Shape matters: the relationship between cell geometry and diversity in phytoplankton - Ryabov, Alexey; Kerimoglu, Onur; Litchman, Elena; Olenina, Irina; Roselli, Leonilde; Basset, Alberto; Stanca, Elena; Blasius, Bernd; Chase, Jonathan (Ecology letters, 2021)
Size and shape profoundly influence an organism’s ecophysiological performance and evolutionary fitness, suggesting a link between morphology and diversity. However, not much is known about how body shape is related to taxonomic richness, especially in microbes. Here we analyse global datasets of unicellular marine phytoplankton, a major group of primary producers with an exceptional diversity of cell sizes and shapes and, additionally, heterotrophic protists. Using two measures of cell shape elongation, we quantify taxonomic diversity as a function of cell size and shape. We find that cells of intermediate volume have the greatest shape variation, from oblate to extremely elongated forms, while small and large cells are mostly compact (e.g. spherical or cubic). Taxonomic diversity is strongly related to cell elongation and cell volume, together explaining up to 92% of total variance. Taxonomic diversity decays exponentially with cell elongation and displays a log‐normal dependence on cell volume, peaking for intermediate‐volume cells with compact shapes. These previously unreported broad patterns in phytoplankton diversity reveal selective pressures and ecophysiological constraints on the geometry of phytoplankton cells which may improve our understanding of marine ecology and the evolutionary rules of life. Cell shape and size are the result of natural selection, but little is known about how shape depends on size and how they affect biodiversity. Using data on dimensions of unicellular marine algae, we show that shape and volume are interrelated: shapes of intermediate‐volume cells range from flattened to extremely elongated, while shapes of small and large cells are always compact. Taxonomic diversity peaks for intermediate‐volume cells with compact shapes, displays a log‐normal dependence on cell volume and decrease exponentially with cell surface extension for elongated or flattened cells.